Perencanaan Jalur Interpretasi Wisata Warisan Sejarah Budaya di Pusat Kota Denpasar - PUTRA, ARIE SETIANA; SUGIARTA, A.A GEDE; YUSIANA, LURY SEVITA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2013)
Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} ABSTRACT Planning of Historical-Cultural Heritage Tourism Interpretation Trail in Downtown Denpasar Region of downtown Denpasar or Denpasar city's is an area of historical-cultural heritage which still exists today. The purpose of this research is to identify and analyze the tourism resources of historical-cultural heritage in downtown Denpasar and plan tourism interpretion trail of historical-cultural heritage in downtown Denpasar. Planning method in this research use the planning stages by Gold (1980) namely preparation, inventory data, analysis , synthesis, concept and planning. Methods of data collection used in this research are observation , interviews and questionnaires , and literature. Sites of historical- cultural heritage in downtown Denpasar there are twelve (12) sites are Monument and Square of Puputan Badung, Catur Muka Sculpture, Office of the Governor house, Mayor's Office of Denpasar City, Jagatnatha Temple, Bali Museum, Inna Bali Hotel, Palace of Satria, Bird Market of Satria, Kumbasari Market and Badung Market, Chinatown of Gajah Mada, and Palace of Pemecutan. Analysis of three aspects, potensial area is Monument and Square of Puputan Badung, and considerable potential are Inna Bali Hotel, Catur Muka Sculpture, Bali Museum, Jagatnatha Temple, Palace of Satria, Palace of Pemecutan, Kumbasari Market and Badung Market, Bird Market of Satria, Mayor's Office of Denpasar City, Office of the Governor house, and Chinatown of Gajah Mada. Potential area being the main attraction and considerable potential as a tourist attraction supporter. tourism interpretion trail of historical- cultural heritage in downtown Denpasar consists of three (3) themes, namely interpretations trail of first alternative, interpretations trail of second alternative interpretations trail of third alternative. K eyword: planning, tourism interpretion trail, historical-cultural heritage